The Effectiveness of the Transportation Agency's Role in Monitoring Illegal Travel - Ihwan Hamonangan , Alif; Khotami; Ade Febrian, Ranggi (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2024)
This research aims to find out how effective the role of the Rokan Hulu district transportation service is in monitoring illegal travel in the city of Pasir Pengaraian. This study used descriptive qualitative method. The indicators in this research are input, process, output and outcome. This research was conducted at the Rokan Hulu Regency transportation service. Collecting data obtained through interviews, observation, documentation. The author's technique for determining informants uses the snowball sampling method. The snowball sampling method is a technique for taking data sources, initially the number is small and then becomes larger, this is because the few data sources are not able to provide satisfactory data, so look for other informants to use as data sources. Based on the research results, it can be concluded that the effectiveness of the role of the Rokan Hulu Regency Transportation Service in monitoring illegal travel in Pasir Pengaraian City is still not effective and optimal because what happens in the field in the monitoring process is only monitoring actions in routine operations and raids, but these activities are still rare. done. The inhibiting factors or obstacles for the Rokan Hulu district transportation service are that they are still careless in terms of supervision, lack of certainty and schedule in carrying out supervision, limited budget, lack of level of public awareness, and still difficulty for transport drivers in processing permits.